Sulphur transport toward soybean roots in three soils from Minas Gerais State, Brazil - Silva, Davi José; Venegas, Víctor Hugo Alvarez; Ruiz, Hugo Alberto (Pesquisa Agropecuaria Brasileira, 2002)
A greenhouse experiment was carried out to evaluate the mass flow and diffusion contributions on sulphur transport toward soybean roots in soil surface samples (0-20 cm) of three soils collected in Viçosa, Paracatu and Lassance, Minas Gerais State, Brazil. Originally, the soil samples presented 5.0, 1.2 and 1.4 mg dm-3 of available S, respectively, obtained by extraction with a Ca(H2PO4)2 solution containing 500 mg L-1 of P in HOAc 2 mol L-1 solution. A 3x5 factorial layout was used with three soils and five S rates (0, 20, 40, 80 and 160 mg dm-3), disposed in a randomized complete block design, with four replications. Tensiometers controlled the soil water potential in each pot and the potential was maintained around -10 kPa. The mass flow was the main mechanism of S transport to soybean roots. At high concentration in soil solution, the quantities supplied by mass flow were higher than those required by plants. Diffusion process only contributed to transport at low S concentration in soil solution.